2016
DOI: 10.1063/1.4963888
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of defect and dopant abruptness at high electron mobility ZnO homojunctions

Abstract: Due to a strong Fermi-level mismatch, about 10% of the electrons in a 5-nm-thick highly Ga-doped ZnO (GZO) layer grown by molecular beam epitaxy at 250 °C on an undoped ZnO buffer layer transfer to the ZnO (Debye leakage), causing the measured Hall-effect mobility (μH) of the GZO/ZnO combination to remarkably increase from 34 cm2/V s, in thick GZO, to 64 cm2/V s. From previous characterization of the GZO, it is known that ND = [Ga] = 1.04 × 1021 and NA = [VZn] = 1.03 × 1020 cm−3, where ND, NA, and [VZn] are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Figure b shows Cu Zn peak intensity for E B = 3.5 keV, corresponding to ∼80 nm excitation depth within the wire for different diameters. Based on a previous NBE-normalized calibration, near-surface V Zn densities are estimated to be ∼1 × 10 21 cm –3 . However, calibration of Cu Zn densities is not yet available.…”
mentioning
confidence: 99%
“…Figure b shows Cu Zn peak intensity for E B = 3.5 keV, corresponding to ∼80 nm excitation depth within the wire for different diameters. Based on a previous NBE-normalized calibration, near-surface V Zn densities are estimated to be ∼1 × 10 21 cm –3 . However, calibration of Cu Zn densities is not yet available.…”
mentioning
confidence: 99%
“…The defect intensities of this wire calibrated with Hall Effect measurements [54] show that defect intensities at Contact 1 are high enough to enable defect-assisted hopping conduction, whereas the lower densities at Contact 4 permit a Schottky barrier to form [18]. The narrow diameter Contact 5 coupled with n-type carrier compensation by V Zn acceptors increases the depletion width radially to pinch off free carrier transport under the contact.…”
Section: Impact Of Zno Defect Distributions On Electronic Measuremmentioning
confidence: 99%
“…In 2000, Dietl's research team found that manganese-doped ZnO and GaN can obtain room-temperature ferromagnetism according to their calculations [3] and predicted that transition metal-doped ZnO semiconductors are dilute magnetic semiconductors with room-temperature ferromagnetism, which laid the foundation for the research of oxidebased dilute magnetic semiconductors. ZnO, a semiconductor with high-exciton binding energy (60 eV) and wide bandgap (3.37 eV), is magnetic owing to intrinsic defects, as well as the doping effect of rare earth elements and 3d transition metals and other magnetic ions and shows significant application value in the fields of information storage and processing [4][5][6]. However, there are drawbacks, such as a low Curie temperature.…”
Section: Introductionmentioning
confidence: 99%